Emerging Domains for Measuring Health Care Delivery With Electronic Health Record Metadata - Tawfik, Daniel; Rule, Adam; Alexanian, Aram; Cross, Dori; Holmgren, A Jay; Lou, Sunny S; McPeek Hinz, Eugenia; Rose, Christian; Viswanadham, Ratnalekha V N; Mishuris, Rebecca G; Rodríguez-Fernández, Jorge M; Ford, Eric W; et al. (Journal of medical Internet research, 2025)
This article aims to introduce emerging measurement domains made feasible through the electronic health record (EHR) use metadata, to inform the changing landscape of health care delivery. We reviewed emerging domains in which EHR metadata may be used to measure health care delivery, outlining a framework for evaluating measures based on desirability, feasibility, and viability. We argue that EHR use metadata may be leveraged to develop and operationalize novel measures in the domains of team structure and dynamics, workflows, and cognitive environment to provide a clearer understanding of modern health care delivery. Examples of measures feasible using metadata include quantification of teamwork and collaboration, patient continuity measures, workflow conformity measures, and attention switching. By enabling measures that can be used to inform the next generation of health care delivery, EHR metadata may be used to improve the quality of patient care and support clinician well-being. Careful attention is needed to ensure that these measures are desirable, feasible, and viable.